Impact of Job Satisfaction on Intention to Quit: A Study on Customer Service Providers in Commercial Banks - Muralidharan, C.; Venkatram, R.; Krishnaveni, R. (Prabandhan: Indian Journal of Management, 2013)
This paper attempts to evaluate the impact of job satisfaction by examining the intention to quit behavior of customer service providers (CSPs) employed under the financial inclusion programme in different commercial banks. A sample of 120 customer service providers were selected from Salem district of Tamil Nadu, and the respondents were personally interviewed. Research results revealed that there was a negative relationship between level of job satisfaction and the intention to quit behavior among the customer service providers. Further, this study also analyzed the CSP’s major causes of dissatisfaction with their jobs. Finally, some important strategies were suggested for the betterment of the customer service providers employed under the business correspondent model of the financial inclusion programme. This study will be an eye opener for bankers and policy makers, giving an insight as to how to carry forward this financial inclusion model in a more effective manner.